Intercropping system modulated soil–microbe interactions that enhanced the growth and quality of flue-cured tobacco by improving rhizospheric soil nutrients, microbial structure, and enzymatic activities - Zhou, Muqiu; Sun, Chenglin; Dai, Bin; He, Yi; Zhong, Jun (Frontiers in Plant Science, 2023)
As the promotive/complementary mechanism of the microbe-soil-tobacco (Nicotiana tobacum L.) interaction remains unclear and the contribution of this triple interaction to tobacco growth is not predictable, the effects of intercropping on soil nutrients, enzymatic activity, microbial community composition, plant growth and quality were studied, and the regulatory mechanism of intercropping on plant productivity and soil microenvironment (fertility and microorganisms) were evaluated.The results showed that the soil organic matter (OM), available nitrogen (AN), available phosphorus (AP), available potassium (AK), the urease activity (UE) and sucrase activity (SC), the diversity, abundance, total and unique OTUs (operational taxonomic units) of bacteria and fungi as well as plant biomass in T1 (intercropping onion), T2 (intercropping endive) and T3 (intercropping lettuce) treatments were significantly higher than the controls (monocropping tobacco). Although the dominant bacteria and fungi at the phylum level were the same for each treatment, LEfSe analysis showed significant differences in community structure composition and the distribution proportion of each dominant community was different. The Proteobacteria, Acidobacteria, Firmicutes of bacteria and the Ascomycota, Basidiomycetes of fungi in T1, T2 and T3 treatments were higher than the controls.Redundancy analysis (RDA) suggested a close relation between soil characteristic parameters and microbial taxa. The correlation analysis between the soil characteristic parameters and plant showed that the plant biomass were closely related to soil characteristic parameters. In conclusion, the flue-cured tobacco intercropping not only increased plant biomass and improved chemical quality, but also significantly increased rhizospheric soil nutrient and enzymatic activities, optimizing the microbial community composition and diversity of rhizosphere soil. The current study highlighted the importance of microbe-soil-tobacco interactions in maintaining plant productivity and provided the potential fertilization practices in flue-cured tobacco production to maintain ecological sustainability.